2011
DOI: 10.1152/ajpregu.00138.2011
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen regulation of the dopamine-activated GIRK channel in pituitary lactotrophs: implications for regulation of prolactin release during the estrous cycle

Abstract: Prolactin (PRL), synthesized and secreted from lactotrophs of the anterior pituitary gland, is tonically inhibited by hypothalamic dopamine (DA) throughout the female reproductive (estrous) cycle. Our laboratory has shown that DA hyperpolarizes these cells by activating G protein-coupled inwardly rectifying K(+) (GIRK) channels; however, this response is only observed on proestrus. While the cellular mechanisms that allow for functional expression of this unique DA-signaling pathway are unclear, we hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 61 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…An additional major source of variation in oxytocin reactivity to certain social contexts and across individuals is likely related to interactions between the oxytocinergic system and other hormonal and neurotransmitter systems (for reviews see Heinrichs et al, 2009 ; Soares et al, 2010 ; Neumann and Landgraf, 2012 ), such as with cortisol (see Szczepanska-Sadowska, 2008 ; Heinrichs et al, 2009 ), vasopressin (Neumann and Landgraf, 2012 ), estrogens (Amico et al, 1981 ; Zak and Fakhar, 2006 ), prolactin (Christensen et al, 2011 ), endorphins (Dunbar, 2010 ), testosterone (van Anders et al, 2011 ), dopaminergic and serotonergic systems (Skuse and Gallagher, 2009 ). Such interactions may account for different behavioral and motivational states associated with high oxytocin levels in both animal and human studies, for example, relaxed parent-infant interactions that engender affiliative and nurturant—“tend-and-befriend”—motivations, compared with in-group vs. out-group interactions that engender more affiliative and defensive—“tend-and-defend” motivations (Taylor et al, 2006 ; Campbell, 2008 ; Ross and Young, 2009 ; van Anders et al, 2011 ; De Dreu, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…An additional major source of variation in oxytocin reactivity to certain social contexts and across individuals is likely related to interactions between the oxytocinergic system and other hormonal and neurotransmitter systems (for reviews see Heinrichs et al, 2009 ; Soares et al, 2010 ; Neumann and Landgraf, 2012 ), such as with cortisol (see Szczepanska-Sadowska, 2008 ; Heinrichs et al, 2009 ), vasopressin (Neumann and Landgraf, 2012 ), estrogens (Amico et al, 1981 ; Zak and Fakhar, 2006 ), prolactin (Christensen et al, 2011 ), endorphins (Dunbar, 2010 ), testosterone (van Anders et al, 2011 ), dopaminergic and serotonergic systems (Skuse and Gallagher, 2009 ). Such interactions may account for different behavioral and motivational states associated with high oxytocin levels in both animal and human studies, for example, relaxed parent-infant interactions that engender affiliative and nurturant—“tend-and-befriend”—motivations, compared with in-group vs. out-group interactions that engender more affiliative and defensive—“tend-and-defend” motivations (Taylor et al, 2006 ; Campbell, 2008 ; Ross and Young, 2009 ; van Anders et al, 2011 ; De Dreu, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using transneuronal markers have shown that exposure to male murine pheromones activates gonadotropin-releasing hormone (GnRH) neurons in females [22], thus stimulating the secretion of follicle-stimulating hormone (FSH) and luteinizing hormone (LH), which enhances the secretion of oestrogen and progesterone. Studies have also shown that oestrogen stimulates prolactin secretion by upregulating dopamine-activated K þ channels in pituitary lactotrophs, producing increased levels of the hormone typical of the proestrous stage [23,24]. The Whitten effect can be explained by similar pheromonal activation of GnRH neurons and the subsequent modulation of ovarian function by the enhanced production of FSH and LH.…”
Section: Introductionmentioning
confidence: 99%
“…Other receptors linked to this pathway and expressed by anterior pituitary cells include those for adenosine, γ-aminobutyric acid (GABA), serotonin, melatonin and neuropeptide Y. Activation of this pathway opposes the actions mediated by the G s - channels in a cAMP/PKA-independent fashion, leading to hyperpolarization and cessation of AP firing. Interestingly, three of the four mammalian Kir3 channels are specifically induced by estradiol in lactotrophs in proestrus, 27 underlying dopamine effects that are only observed in this stage of the cycle: strong Kir conductance and robust hyperpolarization, the latter playing a critical role in the prolactin secretory rebound that follows dopamine withdrawal. 28 A novel mechanism has been recently described for endothelin ETA and dopamine D2 receptors in lactotrophs.…”
Section: Aguirre-1611032 978-0-12-408134-5 00002mentioning
confidence: 99%